2020
DOI: 10.1186/s12879-020-05256-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning reveals that Mycobacterium tuberculosis genotypes and anatomic disease site impacts drug resistance and disease transmission among patients with proven extra-pulmonary tuberculosis

Abstract: Background: There is a general dearth of information on extrapulmonary tuberculosis (EPTB). Here, we investigated Mycobacterium tuberculosis (Mtb) drug resistance and transmission patterns in EPTB patients treated in the Tshwane metropolitan area, in South Africa. Methods: Consecutive Mtb culture-positive non-pulmonary samples from unique EPTB patients underwent mycobacterial genotyping and were assigned to phylogenetic lineages and transmission clusters based on spoligotypes. MTBDRplus assay was used to searc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Sibandze et al investigated spoligotypes involved in extrapulmonary tuberculosis infections in South Africa, a region with one of the highest tuberculosis disease burdens [ 23 ]. They cultured isolates and clustered M. tb strains into four lineages: East Asian (1 case), East African (1 case), Euro-American (5 cases), and an orphan lineage (3 cases), which was considered nonclustered due to unmatched genetic strains.…”
Section: Molecular and Cellular Background Of Ctbmentioning
confidence: 99%
See 1 more Smart Citation
“…Sibandze et al investigated spoligotypes involved in extrapulmonary tuberculosis infections in South Africa, a region with one of the highest tuberculosis disease burdens [ 23 ]. They cultured isolates and clustered M. tb strains into four lineages: East Asian (1 case), East African (1 case), Euro-American (5 cases), and an orphan lineage (3 cases), which was considered nonclustered due to unmatched genetic strains.…”
Section: Molecular and Cellular Background Of Ctbmentioning
confidence: 99%
“…They found that cutaneous, lymphadenitis, and meningitis cases were significantly more likely to be associated with drug resistance, with 45% of sampled cutaneous TB cases demonstrating pan-resistance and 63% of cases with Rifampin and/or MDR-TB resistance. They also found that there was no association between drug resistance and spoligotypes for any resistance [ 23 ].…”
Section: Molecular and Cellular Background Of Ctbmentioning
confidence: 99%
“…In the Kingdom of Eswatini, TB notification and incidence rates have been decreasing steadily in the past decade, from a peak incidence of 1,190 per 100,000 populations in 2009 to a low incidence rate of 329 per 100,000 populations in 2018 [ 2 ]. Notifications of drug resistant TB (DR-TB) mirrored those of drug-susceptible TB for the same period; however, DR-TB has not been adequately tracked by most TB programs in the Sub-Saharan Africa region, until recently [ 3 ]. The proportion of persons developing DR-TB while on treatment, including those with multidrug resistant TB (MDR-TB), increased over the years in Eswatini.…”
Section: Introductionmentioning
confidence: 99%